The potential for domestic thermal insulation retrofits on the South African Highveld - Matandirotya, Newton R; Cilliers, Dirk P; Burger, Roelof P; Language, Brigitte; Pauw, Christian; Piketh, Stuart J (Clean Air Journal, 2019)
The South African Highveld is a portion on the inland plateau characterized by low winter ambient temperatures. Studies done in several climatic regions around the world have found a positive relationship between inadequate housing and low indoor temperatures during the winter season. Prolonged exposure to low indoor temperature is a threat to human physical health. This study characterizes indoor human thermal comfort conditions in typical low-income residential dwellings during the winter season. Mapping indoor human thermal comfort can assist in exploring the potential for domestic thermal insulation retrofits interventions. In-situ temperature measurements were done in 2014, 2016 and 2017 across three Highveld settlements of kwaZamokuhle, kwaDela, and Jouberton. The sample included a mixture of old (pre-1994), post 1994 Reconstruction and Development Programme (RDP) as well as non-RDP structures. Findings were that 88% of sampled dwellings in Jouberton 2016, 86% in Jouberton 2017, 62% in kwaDela and 58% in kwaZamokuhle had daily mean temperatures below the WHO guideline of 18°C. These low indoor temperatures indicate poor insulation in these sampled dwellings. Across all settlements, insulated dwellings had higher daily mean indoor temperatures than non-insulated dwellings. These findings indicate the potential to use thermal insulation retrofits in improving indoor thermal conditions as the majority of dwellings are non-insulated thereby exposing occupants to low indoor temperatures.